Odprta znanost in kako v njej prepoznajo svojo vlogo slovenski visokošolski knjižničarji - Kuhar, Maja (Knjižnica, 2018)
Open science represents a modern communication of the 21st century science and assumes the openess of all phases of research work. It has developed on the initiative of researchers, at the end of last century. Upon its enactment it is necessary to transform the role of an academic librarian. The aim of this paper is to present the role of an academic librarian in the field of open science and how it is perceived by Slovenian academic librarians. We conducted a survey among academic librarians at three public universities in Slovenia in the summer of 2017. Data were obtained using a web-based questionnaire, we analysed 64 questionnaires, that were fully filled out. The results of the survey showed that most of the interviewees understood the notion of open science merely as open access to scientific publications and research data and metadata related to them. Moreover, the interviewees highlighted the construction of a repository as a very important task in the work of an academic librarian in the field of open science. We found, however, that the latter is more important to librarians working at the University of Maribor than those who work at the University of Ljubljana. Only few recognized the importance of the role of the librarian in checking the content similarity, and only one librarian emphasized the need for an active involvment with advising on the copyrights. More than half of the interviewees claimed that the tasks in their library related to open science are carried out by someone qualified for this type of work. We believe that academic librarians in Slovenia could be more involved in performing the tasks related to open science. Professional meetings and open access web portals serve as excellent means of providing knowledge to librarians.
Keywords: academic libraries; odprta znanost; odprti dostop; open access; open science; the role of a librarian; visokošolske knjižnice; vloga knjižničarja